SHADOW TEACHER FOR SPECIAL NEEDS STUDENTS: CASE STUDY CLASS VI TAMAN MUDA IBU PAWIYATAN YOGYAKARTA - Maratul Qiftiyah; Wina Calista (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2021)
This research is to describe the shadow teacher for students with special needs at Taman Muda Ibu Pawiyatan Yogyakarta Elementary School. This type of research is qualitative research. This is a qualitative descriptive study which produces descriptive data in the form of words based on detailed and in-depth field research. The subject of this study was the shadow teacher in class VI. Data collection techniques using observation and interviews. As for the data analysis which is done which includes: data reduction, data presentation, and concluding. Based on the results of the study it can be concluded that the shadow teacher who accompanies students with special needs (mild intellectual impairment) in class VI is doing an authoritarian accompaniment. The mentoring makes students experience pressure when learning, it is not uncommon for students to cry, and leave the classroom when learning. Also, the shadow teacher's actions disturb other students. That is what some parents in class IV agreed not to involve shadow teachers in the learning process in class.